A Structural Study on the Specificity of F1 Protease - Muhamad, Azira (2005)
Specificity studies of a thermostable alkaline serine protease F1 with its substrates were carried out through computational docking method. Structures of a series of synthetic peptide substrates were docked to the active site of the homology modelled F1 protease using AutoDock 3.0.5. The resulting clusters of the substrates that were docked were analysed by inspecting the energetic results and the orientation of each cluster to determine the arrangement of productive binding. The amino acids of the binding site that participated in the hydrophobic and hydrogen-bond interactions were also determined. Docking results showed that all substrates tested bound near the catalytic residues with SucAAPFpNA, the biggest substrate, showing the most negative docked energy value @docked = -18.75 kcal/mol). Smaller substrates such as GpNA and AApNA showed higher docked energy (Edocked = -7.77 kcal/mol and -8.77 kcal/mol, respectively). The best docked structure of each substrate was determined from the clusters. It was found that most of the lowest Edocked conformations display the best docked orientations with respect to the least distance calculated between the carbonyl carbon of the substrate PI residue and y-oxygen of the Ser226 catalytic triad. From the results, it also demonstrated that S1, S2 and S4 subsites of the enzyme play a critical role in determining the substrate specificity of F1 protease from the point of view that bigger-sized substrates such as SucAAPFpNA and SucAAPLpNA showed more favourable Edocked. This work also support the hypothesis that the catalytic serine and histidine residues were essential in catalysis as well as in stabilizing the enzymesubstrate complex for binding. Validation of computational study was carried out through biochemical assay. It was found that SucAAPFpNA was the most preferred substrate for the enzyme with specific activity of 3.079 U/mg followed by SucAAPLpNA at 1.016 U/mg. SucAAPFpNA was also observed to show the highest binding affinity towards the protease (Km = 1.26mM) and the highest catalytic ratio (1.226 min-l.rnM-1) compared to the other substrates tested. Similar to computational observations, smaller peptides showed lower specific activity and binding affinity towards the protease. Rank-order of the substrates tested for the docking and experimental methods were found to be similar for the top two substrates, with lesser agreement for the other substrates.